Membangun Generasi Sadar Hukum: Urgensi Pendidikan Hukum bagi Remaja dalam Penegakan Hukum di Indonesia - Listyarini, Dyah; Sholihah, Dwi Imroatus; Hidayat, Fauzan; Raharjo, Sri Budi (Universitas Muhammadiyah Metro, 2025)
Indonesia, as a country based on the rule of law, places law at the foundation of every aspect of social, national, and state life. However, reality shows that the level of law violations among teenagers, especially high school students, is still quite high. One of the factors behind this is their lack of understanding of the law and lack of awareness of the consequences of their actions. This study aims to analyze the role of legal education in shaping legal awareness and supporting the law enforcement process from an early age. The research method used is a sociological juridical approach with data collection through direct interviews with high school students. The results show that legal education is not only important to be included in the school curriculum, but also needs to be implemented through legal counseling programs involving law enforcement officials and related agencies. Through the implementation of legal education, students can understand the values of justice, recognize prohibited and permitted acts, and internalize an attitude of legal compliance. Thus, legal education plays a strategic role in shaping a young generation that is legally aware and contributes to the creation of more effective law enforcement in Indonesia.